Proposed Business Strategy Using Strategic Management Approach for Business Growth (Case Study of PT. Guna Olah Niaga) - Raka Aludi Haryanto; Muhammad Yorga Permana (Green Publisher Indonesia, 2026)
Agriculture contributes 13–15% of Indonesia’s GDP and employs a large share of the population, yet decades of reliance on chemical fertilizers have caused serious soil and environmental degradation. To support sustainable farming, PT Guna Olah Niaga (PT GON), a Bandung-based start-up, produces liquid organic fertilizer from invasive and discarded biomass such as water hyacinth and vegetable waste; however, the company faces strategic challenges including limited production capacity, low market credibility, financial constraints, and weak product differentiation. This study develops sustainable business strategies for PT GON using a qualitative case study approach, combining interviews with founders, farmers, government officials, and industry practitioners, supported by secondary data. Internal analysis (Value Chain, VRIO) identifies strengths in waste-based innovation and founder expertise, but weaknesses in standardization, scalability, and financing. External analysis (PESTEL, Porter’s Five Forces) highlights opportunities in rising awareness of sustainable farming and growing B2B demand, alongside threats from subsidized chemical fertilizers, intense competition, and farmers’ hesitation toward new organic inputs. Through SWOT–TOWS synthesis, three strategic pillars emerge: (1) operational enhancement through standardization, automation, and quality assurance; (2) market expansion through partnerships, demonstration plots, and benefit-driven branding; and (3) innovation and capability development via continuous R&D and collaboration with research institutions. These are operationalized through a Balanced Scorecard (BSC) with KPIs for 2026–2028. Overall, the study concludes that strengthening operational excellence, strategic market penetration, and long-term capability building can significantly enhance PT GON’s competitiveness and support its transition into a scalable, sustainable enterprise in Indonesia’s organic fertilizer industry.